The Development of Open University New Generation Learning Model Using Research and Development for Atomic Physics Course PEFI4421 - *, Prayekti (IJRDO-Journal of Applied Science, 2017)
This research was aimed at developing printed teaching materials of Atomic Physics PEFI4421Course using Research and Development (R & D) model; which consisted of three major set ofactivities. The first set consisted of seven stages, the second set consisted of one stage, and the thirdset consisted of seven stages. This research study was scheduled at the first year of the coursedevelopment. This study concluded that (1) the teaching materials used for Atomic Physics CoursePEFI4421 were necessary to be revised and updated since many of the materials were outdated, (2)the materials and concepts of Atomic Physics were hard to be learned by the students independentlywithout face-to-face tutorials, (3) the exercises used in the handout were not clearly described indetail making them to be difficult to be completed, and (4) the physical presentation of the coursematerials needed improvement because they are lack of attractiveness for the students to use